2018
DOI: 10.1016/s1473-3099(18)30219-6
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance among migrants in Europe: a systematic review and meta-analysis

Abstract: SummaryBackgroundRates of antimicrobial resistance (AMR) are rising globally and there is concern that increased migration is contributing to the burden of antibiotic resistance in Europe. However, the effect of migration on the burden of AMR in Europe has not yet been comprehensively examined. Therefore, we did a systematic review and meta-analysis to identify and synthesise data for AMR carriage or infection in migrants to Europe to examine differences in patterns of AMR across migrant groups and in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
87
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 73 publications
(251 reference statements)
9
87
0
1
Order By: Relevance
“…Similar to our data, a recently published review on AMR among European migrants found a high prevalence of MRSA (8%) and resistant Gram-negative bacteria (27%), concluding that living conditions, access to healthcare and AMR detection should be improved in this high-risk population [75]. In line with our findings, data from Germany suggest that ESBL-colonisation seems to be common among refugees, whereas CPE are rarely detected [76].…”
Section: Epidemiology and Infectionsupporting
confidence: 91%
“…Similar to our data, a recently published review on AMR among European migrants found a high prevalence of MRSA (8%) and resistant Gram-negative bacteria (27%), concluding that living conditions, access to healthcare and AMR detection should be improved in this high-risk population [75]. In line with our findings, data from Germany suggest that ESBL-colonisation seems to be common among refugees, whereas CPE are rarely detected [76].…”
Section: Epidemiology and Infectionsupporting
confidence: 91%
“…This systematic review shows that the majority of the included studies analysing the burden of AMR on migrants as compared to the local population of the host country, present a higher prevalence in the migrant population. These results con rm the emerge of the circulation of resistant strains among migrant groups being highlighted in previous research and reports of international health organisations like the WHO [15,16,[22][23][24].…”
Section: Summary Of Main Ndingssupporting
confidence: 85%
“…The review found a high percentage of resistant strains have been circulating among refugees and asylum seekers. Focusing in Europe, Nellums et al [16] analysed 23 observational studies that reported on migration and AMR in 2319 migrants, including methicillin-resistant Staphylococcus aureus and antibiotic-resistant Gram-negative bacteria. The results showed a combined prevalence of any infection by resistant bacteria in migrants of 25.4% (I2 = 98%), with refugees and asylum seekers having a signi cantly higher risk than other groups of migrants and the general population (33% vs. 6%, I2 = 92% and 98%, respectively), with no evidence of AMR transmission from migrants to host populations.…”
mentioning
confidence: 99%
“…Immigration into Europe from countries with high levels of antibiotic resistance has contributed to greater and changing resistance patterns. 6 Plasmid-acquired carbapenemases in Enterobacteriaceae are being identified at an alarming rate in Europe. 7,8 Although their hydrolysis spectrum may vary, these enzymes hydrolyze most β-lactams including carbapenems and are mostly of the KPC, VIM, NDM, and OXA-48 types.…”
mentioning
confidence: 99%